PELATIHAN PENERAPAN ARTIFICIAL INTELLIGENCE (AI) UNTUK KEGIATAN BELAJAR MENGAJAR PADA PENDIDIKAN MENENGAH KEJURUAN - Muhammad Faqih Rohmani; Pratama, Wahyu (Universitas Pamulang, 2026)
This Community Service activity aims to improve the literacy and skills of educators at Al-Amanah Vocational High School, Sindang Jaya, Tangerang, Banten, in understanding and applying Artificial Intelligence (AI) technology to teaching and learning activities. The training focused on the use of two main platforms, ChatGPT and Google Gemini, as tools for developing teaching materials, creating questions, and conducting interactive classroom simulations. The implementation method used interactive lectures, demonstrations, and hands-on training. The results showed a significant improvement in participant skills, with 85% of teachers able to implement Al to support learning and create digital teaching materials. Furthermore, 98% of participants showed a significant increase in AI understanding, and 92% stated they were ready to implement AI in the learning process. The activity also resulted in the formation of the Al-Amanah Vocational High School Smart Teacher community as a platform for the sustainability of training and sharing good practices among teachers. The results emphasized how the offered solution successfully addressed the partner's problem. Keywords: Artificial Intelligence, ChatGPT, Gemini, Digital Learning, Vocational High School Teachers